Design and validation of a key performance indicator dashboard for equity in community and retail pharmacy services in Pakistan - Muhammad Hammad; Rasikh Arif; Ali Zeb Khan; Ali Nasir (PLoS ONE, 2026)
Background Community and retail pharmacies are essential to primary healthcare delivery in Pakistan; however, significant disparities in workforce distribution, medicine availability, and service quality persist between urban and rural settings. The absence of standardized performance monitoring systems limits the ability to identify and address these inequities. Objective To design, develop, and validate a key performance indicators (KPI) dashboard for monitoring equity in community and retail pharmacy service delivery in Pakistan. Methods A multi-phase methodological study was conducted. Phase I involved qualitative needs assessment using semi-structured interviews with pharmacists, technicians, and administrators (n = 28) to identify service gaps. Phase II employed a modified Delphi technique with expert panel consensus to refine KPIs. Phase III included dashboard development using Microsoft Power BI. Phase IV comprised validation through content validity index (CVI) assessment and usability testing using the System Usability Scale (SUS). Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. Results Eleven KPIs across workforce, efficiency, quality, safety, availability, and equity domains were finalized. Significant disparities were observed between urban and rural pharmacies, including higher stock-out duration (13.1 vs 6.2 days), lower counseling rates (55% vs 78%), and poorer workforce ratios (1:120 vs 1:65). The dashboard demonstrated high usability (SUS score: 82.5) and strong content validity (S-CVI/Ave: 0.89). Conclusion The developed KPI dashboard provides a feasible and scalable tool for real-time monitoring of pharmacy performance and equity. Its implementation can support evidence-based decision-making and improve equitable pharmaceutical service delivery in Pakistan.